The Impact of Competitive Asymmetric Sports on the Development of Idiopathic Scoliosis in Young Athletes: A Literature Review - Jakubowska, Paulina; Szaryński, Mikołaj; Jakubowska, Martyna; Prokopczyk, Kamila; Wasilczuk, Antoni; Peszt, Michał Józef; Matuszewska, Julia; Poręba, Martyna; Poręba, Kacper; Rusiłowicz, Rafał; Lewandowska-Mackiewicz, Aleksandra (Quality in Sport, 2025)
This review examines how participation in competitive asymmetric sports influences the development and progression of adolescent idiopathic scoliosis (AIS). Studies show that sports involving repetitive unilateral movements, such as gymnastics, ballet, tennis, volleyball, basketball, and football are associated with higher AIS prevalence and increased muscle and postural asymmetries. The highest rates, reaching 30–35%, occur in ballet dancers and gymnasts. Factors such as early training initiation, high training intensity, hypermobility, low skeletal maturity, and rapid growth further elevate risk. While asymmetric sports may promote curve progression, regular recreational physical activity demonstrates a protective effect, reducing both progression and the need for bracing. The review emphasizes the importance of monitoring posture, adjusting training loads, and implementing compensatory exercises in young athletes engaged in asymmetric disciplines.